ANALISIS PUTUSAN PENGADILAN ATAS PEMBERIAN IZIN POLIGAMI OLEH PENGADILAN AGAMA SURABAYA : Studi Putusan Nomor 2469/Pdt.G/2022/PA.Sby - Raffly Fadilla; Hervina Puspitosari (Gapenas Publisher, 2023)
A good judgement is the one that conforms to the applicable rules. The analysis of the court’s judgement regarding the granting of polygamy permit aims to examine and analyze the legal and social aspects of the judgement, as well as the legal considerations used by the Panel of Judges. This research employs a normative legal research method that relies on the study of legal literature and interviews as supporting data. The approach used in this study is a case approach based on primary, secondary, and tertiary legal materials. The results of this research indicate that the Panel of Judges considers both legal and humanitarian aspects in their judgements. Furthermore, the polygamy permit application with Case Number 2469/Pdt.G/2022/PA.Sby, although meets the requirement for polygamy permits under both civil and Islamic law, is deemed incompatible with humanitarian values due to the applicant’s income, which is not considered sufficient for practicing polygamy